2018
DOI: 10.1002/chem.201801452
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Complexes with Oxido and Corrolato Ligands: Metal‐Based Redox Processes versus Ligand Non‐Innocence

Abstract: Metal- versus ligand-centered redox processes and the effects of substituents on the ligands on the spectroscopic properties of the metal complexes are at the heart of research on metal complexes with non-innocent ligands. This work presents three examples of chromium complexes that contain both oxido and corrolato ligands, with the substituents on the corrolato ligands being different in the three cases. Combined X-ray crystallographic, electrochemical, UV/Vis/NIR/EPR spectroelectrochemical, and EXAFS/XANES m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“… 23 In the oxo[10-( p -hydroxyphenyl)-5,15-bis( m -bromophenyl)corrolato]chromium(V) derivative, the chromium atom is axially displaced from the N4 corrole plane by 0.57 Å. 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 In the oxo[10-( p -hydroxyphenyl)-5,15-bis( m -bromophenyl)corrolato]chromium(V) derivative, the chromium atom is axially displaced from the N4 corrole plane by 0.57 Å. 23 …”
Section: Resultsmentioning
confidence: 99%
“…This displacement is comparable to the other literaturereported oxo(corrolato)chromium(V) derivatives. 23 In the oxo[10-(p-hydroxyphenyl)-5,15-bis(m-bromophenyl)corrolato]chromium(V) derivative, the chromium atom is axially displaced from the N4 corrole plane by 0.57 Å. 23 The chromium−nitrogen (pyrrolic) bond lengths are in the range of 1.988−1.997 Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, while CrO triarylcorroles generally do not exhibit skeletal bond length alternations, 48 an electron-rich CrO-triarylcorrole with a 10-p-hydroxyphenyl substituent does, emphasizing the subtlety of the matter. 49 To complement the above crystallographic findings, we carried out scalar-relativistic DFT calculations using the Zeroth Order Regular Approximation (ZORA) to the Dirac equation (as implemented in the ADF program system) and all-electron STO-TZ2P basis sets on four model systems - the optimized geometries showed that the alternations are smaller in magnitude than for Mo[TPC]Cl 2 , potentially indicating a lower degree of corrole •2− character in the W case.…”
Section: Molecular Structurementioning
confidence: 99%
“…This substituent effect plays crucial roles in determining the stability and the redox property of metal corroles, which are both significant factors considered in the catalysis of small molecule activation reactions. Many articles have been published regarding the influence of meso -substituent on the electrochemical and spectral properties of metal corroles. Notably, electron-withdrawing groups can decrease the electron density on the aromatic corrole macrocycle, and thus increase their tolerance of oxidative degradation.…”
Section: Structure Effects On Her Oer and Orrmentioning
confidence: 99%